Effect of Nanoscale Zero-Valent Iron on Arsenic Bioaccessibility and Bioavailability in Soil - Chen, Shuo; Han, Lei; Wang, Qiu; Liu, Chenglang; Liu, Yuzhen; Li, Jie (Frontiers in Chemistry, 2022)
Hand-to-mouth activity is considered to be the main way for children to come into contact with contaminated soil, and bioavailability is an important factor affecting their health risk. To reduce soil As risk to humans by oral exposure, nanoscale zero-valent iron (nZVI) has been extensively studied for immobilizing As-contaminated soil, but its efficiency has not been investigated using in vitro assay and its influence on As-RBA. In this study, two contaminated soil samples (A and B) were amended with 1% and 2% (w/w) nZVI for 56 days to study its effect on As fraction by sequence extraction, As bioaccessibility by SBRC assay, and As relative bioavailability (RBA) by the mouse liver and kidney model. Based on the sequence extraction, the As associated with the E1 (exchangeable fraction) and C2 (carbonate fraction) fractions were decreased from 3.00% to 1.68% for soil A and from 21.6% to 7.86% for soil B after being treated with 2% nZVI for 56 days. When assessing As bioaccessibility in all soils treated with nZVI by SBRC assay, it was found that As bioaccessibility was significantly higher in the gastric phase (GP) and lower in the intestinal phase (IP) (p < 0.05), and the bioaccessible Fe concentration decreased significantly from the gastric to intestinal phase at the same time. Based on the mouse liver–kidney model, the As-RBA in soil A increased from 21.6% to 22.3% and 39.9%, but in soil B decreased from 73.0% to 55.3% and 68.9%, respectively. In addition, there was a significant difference between As bioaccessibility based on GP or IP of SBRC assay and As-RBA in two soils after being treated with nZVI for 56 days. To more accurately assess the effects of nZVI human arsenic exposure, As-RBA should be considered in concert with secondary evidence provided through fraction and bioaccessibility assessments. In addition, it is necessary to develop a suitable in vitro assay to predict As-RBA in nZVI-amended soils.